Obesity prevalence among healthcare professionals in England: a cross-sectional study using the Health Survey for England - Richard G Kyle; Jane Wills; Catherine Mahoney; Louise Hoyle; Muireann Kelly; Iain M Atherton (BMJ Open)
Objective To estimate obesity prevalence among healthcare professionals in England and compare prevalence with those working outside of the health services.Design Cross-sectional study based on data from 5 years (2008–2012) of the nationally representative Health Survey for England.Setting England.Participants 20 103 adults aged 17–65 years indicating they were economically active at the time of survey classified into four occupational groups: nurses (n=422), other healthcare professionals (n=412), unregistered care workers (n=736) and individuals employed in non-health-related occupations (n=18 533).Outcome measure Prevalence of obesity defined as body mass index ≥30.0 with 95% CIs and weighted to reflect the population.Results Obesity prevalence was high across all occupational groups including: among nurses (25.1%, 95% CI 20.9% to 29.4%); other healthcare professionals (14.4%, 95% CI 11.0% to 17.8%); non-health-related occupations (23.5%, 95% CI 22.9% to 24.1%); and unregistered care workers who had the highest prevalence of obesity (31.9%, 95% CI 28.4% to 35.3%). A logistic regression model adjusted for sociodemographic composition and survey year indicated that, compared with nurses, the odds of being obese were significantly lower for other healthcare professionals (adjusted OR (aOR) 0.52, 95% CI 0.37 to 0.75) and higher for unregistered care workers (aOR 1.46, 95% CI 1.11 to 1.93). There was no significant difference in obesity prevalence between nurses and people working in non-health-related occupations (aOR 0.94, 95% CI 0.74 to 1.18).Conclusions High obesity prevalence among nurses and unregistered care workers is concerning as it increases the risks of musculoskeletal conditions and mental health conditions that are the main causes of sickness absence in health services. Further research is required to better understand the reasons for high obesity prevalence among healthcare professionals in England to inform interventions to support individuals to achieve and maintain a healthy weight.